2014
DOI: 10.1007/s11356-014-2850-7
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of PAHs and trace metals in urban stormwater sediments: combination of density fractionation, mineralogy and microanalysis

Abstract: Sediment management from stormwater infiltration basins represents a real environmental and economic issue for stakeholders due to the pollution load and important tonnages of these by-products. To reduce the sediment volumes to treat, organic and metal micropollutant-bearing phases should be identified. A combination of density fractionation procedure and microanalysis techniques was used to evaluate the distribution of polycyclic aromatic hydrocarbons (PAHs) and trace metals (Cd, Cr, Cu, Ni, Pb, and Zn) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Cd, Cr, Cu, Ni, Pb, and Zn) for three urban storms water basin sediments. 30 The sensibility of microanalysis allows the authors to identify pollutantbearing phases in their samples. Their results confirm that PAHs are found in the lightest fractions (d < 1.9, 1.9 < d < 2.3 g cm −3 ) whereas trace metals are equally distributed within the light, intermediary, and highest fractions (d < 1.9, 1.9 < d < 2.3, 2.3 < d < 2.6, and d > 2.8 g cm −3 ) and are mostly in the 2.3 < d < 2.6 g cm −3 fraction.…”
Section: Edx Microanalysis In Heavy Metals Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cd, Cr, Cu, Ni, Pb, and Zn) for three urban storms water basin sediments. 30 The sensibility of microanalysis allows the authors to identify pollutantbearing phases in their samples. Their results confirm that PAHs are found in the lightest fractions (d < 1.9, 1.9 < d < 2.3 g cm −3 ) whereas trace metals are equally distributed within the light, intermediary, and highest fractions (d < 1.9, 1.9 < d < 2.3, 2.3 < d < 2.6, and d > 2.8 g cm −3 ) and are mostly in the 2.3 < d < 2.6 g cm −3 fraction.…”
Section: Edx Microanalysis In Heavy Metals Identificationmentioning
confidence: 99%
“…Their results confirm that PAHs are found in the lightest fractions (d < 1.9, 1.9 < d < 2.3 g cm −3 ) whereas trace metals are equally distributed within the light, intermediary, and highest fractions (d < 1.9, 1.9 < d < 2.3, 2.3 < d < 2.6, and d > 2.8 g cm −3 ) and are mostly in the 2.3 < d < 2.6 g cm −3 fraction. 30 …”
Section: Edx Microanalysis In Heavy Metals Identificationmentioning
confidence: 99%
“…Some investigations indicate that 11%-17% of the PAH content in the road runoff was dissolved, and the rest was particle-bound [48], and therefore after sedimentation would end up in the SWRP sediments. Of the particle-bound fraction, El-Mufleh et al [49] found that roughly half of the PAH was associated with particles lighter than 1.9 g•cm −3 , a density that contributed the main part of the organic matter in the investigated samples. A screening study of sediments from 70 Danish SWRPs found that 83% of the samples had total PAH concentrations below 4 mg•(kg•DM) −1 , and hence were to be treated as unpolluted soil with respect to this contaminant [39].…”
Section: Sedimentsmentioning
confidence: 95%
“…In polluted aquatic sediments, elevated concentrations of cadmium, chromium, copper, nickel, zinc or lead are found most often. Their presence in the aquatic environment may result both from natural processes occurring in the atmosphere, which provides a dispersed source of pollutants, and from anthropogenic processes (transportation, industries, mining, municipal and industrial sewage, and also agriculture) which constitute point emission sources [7][8][9]. Polycyclic aromatic hydrocarbons are on the list of the most dangerous substances, which was compiled by the American Environmental Protection Agency (EPA).…”
Section: Introductionmentioning
confidence: 99%